2021
DOI: 10.1007/s10973-021-10574-z
|View full text |Cite
|
Sign up to set email alerts
|

Exergoeconomic analysis of photovoltaic thermal systems based on phase change materials and natural zeolites for thermal management

Abstract: Conventional photovoltaic thermal (PVT) systems provide unstable thermal energy, which changes throughout the day. In PVT systems, phase change materials (PCMs) and heat storage materials could be used to make thermal energy more stable and provide longer-term thermal energy. In the present study, exergoeconomic analysis of PVT systems integrated with natural zeolites has been firstly carried out, and the results were compared with the results of PVT systems integrated with PCM and conventional one. PVT system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Normalized root mean square was used to check and evaluate the performance of the ANN [ 33 ]. Three inputs (L: load, S: speed, D: distance) were used to construct the ANN architecture for all the samples in which weight loss (w) was the output, and the hidden layer indicated that an interaction between the neurons was not visible [ 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Normalized root mean square was used to check and evaluate the performance of the ANN [ 33 ]. Three inputs (L: load, S: speed, D: distance) were used to construct the ANN architecture for all the samples in which weight loss (w) was the output, and the hidden layer indicated that an interaction between the neurons was not visible [ 54 , 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The free convection happens due to the buoyancy-driven forces which emerge because of the distinction in temperature gradients and densities inside the liquid. The convective heat energy transfer has been remained an attractive research field because of its wide scope of uses in engineering and industry, Sowmya et al [1], Nehad Ali Shah et al [2], Kassai et al [3]. The application of an external magnetic field changes the liquid flow shape.…”
Section: Introductionmentioning
confidence: 99%